Dismantling Roadblocks to Equity? The Impact of Advanced Placement Initiatives on Black and Latinx Students' Access and Performance. Issue 5 (May 2019) - Roegman, Rachel; Allen, David; Hatch, Thomas
Background: Increasing access to Advanced Placement (AP) coursework has been a long-term goal of the College Board and many districts across the country, yet achieving this goal has remained elusive, particularly for African American and Latinx youth and youth in poverty. Purpose: In this study, we analyze the work of five districts that have identified inequities in AP participation and developed initiatives to address these inequities. We examine these districts' strategies, as well as their impact on both access to AP coursework and success on AP exams. We consider how efforts to increase access to AP have affected different racial/ethnic student groups. Participants: The five districts are led by superintendents who were members of the Instructional Leaders Network (ILN), a statewide network that focuses on supporting superintendents' system-wide, equity-focused improvement. The districts vary in demographics, size, and socioeconomic status. Data Collection and Analysis: This mixed methods study includes five years of AP enrollment and performance data for four districts, and two years of data for one district. We also identified two of these districts as case studies of AP initiative development and implementation and conducted a series of interviews with administrators from the districts over the five years of the study. We analyzed quantitative data descriptively and used Bonilla-Silva's (2018) concept of color-blind racism to analyze these data in relation to the interview data. Findings: All districts adopted strategies focused on students as a whole, which for the most part led to an increase in access for all racial/ethnic groups, but no consistent pattern of reducing over- or under-representation. In terms of outcomes, in some districts, more students received scores of 3 or higher from all racial/ethnic groups, but disparities in average test scores remained. Additionally, across all districts, Black students continued to receive the lowest scores. Conclusions: As school districts, individual high schools, and the College Board continue their focus on increasing equity in both access and performance, their approaches need to involve ongoing data collection and evaluation on how different programs and initiatives are positively or negatively affecting student populations that have been traditionally under-served as well as students in general. This research demonstrates that color-neutral policies need to be constantly interrogated by K–12 administrators and other stakeholders to ensure that the policies do not reinforce and sustain existing inequities. If districts seek to target groups of students who are underserved, they need to consider strategies and policies that explicitly and directly address those groups.